2023
DOI: 10.1186/s12939-023-01843-4
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare discrimination and factors associated with gender-affirming healthcare avoidance by transgender women and transgender men in Thailand: findings from a cross-sectional online-survey study

Abstract: Background Although discriminatory experiences of transgender people seeking healthcare services have been well-documented in several studies, differentiating those experiences based on gender identity/expression and related factors has been limited. The aim of this study was to compare the characteristics, experiences, attitude, and expectation toward accessing healthcare service and healthcare providers of transgender women and transgender men in Thailand. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
(64 reference statements)
0
3
0
Order By: Relevance
“…These findings align with previous studies that also observed that transgender women often obtain medication through unconventional means such as online purchasing without a prescription, sharing among friends or even stealing. 6 , 10 , 25 , 32 Obtaining medications from pharmacies without a prescription is consistent with findings reported by Sekoni et al 12 who found preferences by transgender women in utilising pharmacies to access medication. Seeking advice and recommendations from friends who have encountered similar health issues has also been documented by Augustaitis et al 16 in the United States.…”
Section: Resultssupporting
confidence: 86%
“…These findings align with previous studies that also observed that transgender women often obtain medication through unconventional means such as online purchasing without a prescription, sharing among friends or even stealing. 6 , 10 , 25 , 32 Obtaining medications from pharmacies without a prescription is consistent with findings reported by Sekoni et al 12 who found preferences by transgender women in utilising pharmacies to access medication. Seeking advice and recommendations from friends who have encountered similar health issues has also been documented by Augustaitis et al 16 in the United States.…”
Section: Resultssupporting
confidence: 86%
“…Minority stress theory [19][20][21] is useful for understanding how stigma influences healthcare use among trans Latinas through a focus on distal (e.g., discrimination and victimization) and proximal (e.g., internalized and anticipated stigma) minority stressors as well as resilience (i.e., strategies for responding to stress exposure). Minority Stress Theory recognizes that anti-trans stigma can contribute to poorer mental and physical health, including access to and use of health care [19][20][21][22][23][24][25]; this occurs when trans people anticipate or experience mistreatment within healthcare settings, which results in receiving poorer care and healthcare avoidance [8,13,26,27]. Research has also demonstrated that experiencing anti-trans stigma outside of the healthcare context can reduce use of healthcare services [22].…”
Section: Theoretical Considerationsmentioning
confidence: 99%
“…While prior research explored the role of stigma and resilience on healthcare use [18,22,25,26,28], it is unclear how the intersecting forms of stigma experienced by trans Latinas (e.g., related to gender identity, race/ethnicity, and perceived documentation status) may influence use of health care, including general health care experiences and access to medically supervised gender-affirming care. When considering the experiences of trans Latinas, it is important to consider an intersectionality framework [31][32][33][34], which identifies that multiple systems of oppression (e.g., racism, sexism, and cisgenderism) occur simultaneously and reinforce each other in ways that change the experiences of people with multiple marginalized identities.…”
Section: Theoretical Considerationsmentioning
confidence: 99%
“…From this perspective, other important considerations about SDH in the transgender population include, for example, gender. Boonyapisomparn et al observed that transgender women had higher probabilities of accessing and utilizing non-conventional healthcare, such as undergoing procedures in inadequate environments and hormone usage without medical prescription, when compared to transgender men 9 .…”
Section: Introductionmentioning
confidence: 99%